Analisis Pemberdayaan Masyarakat Nelayan Di Desa Kuala Ba’u Kabupaten Aceh SeLatan - fitriani, Dewi; Nasution, Muhammad Arif (Journal of Aceh Aquatic Sciences, 2023)
The aim of this research is to design a community empowerment strategy. The analysis used in this research is a descriptive statistical approach, and AHP consists of five criteria, namely, economic, social, technological, institutional and environmental criteria. Based on the results of the AHP analysis, institutional criteria (22%) are the main priority, followed by economic (22%), social (21%), environmental (20%) and technological (15%). The initial strategy proposed is to form social institutions that operate in the economic sector, for example community cooperatives that manage part of village funds, the next step is to improve the social aspect to minimize the impact of conflicts that can occur in the management of previously established economic institutions, then form an environmentally caring character. and be aware of technology so that the established community empowerment strategy can be sustainable and develop according to technological developments.